PENGARUH BIAYA PRODUKSI TERHADAP PENDAPATAN USAHATANI PADI LADANG DI KAMPUNG LINGGANG MELAPEH KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT (The Influence of Production Cost to Swidden Cultivation Income in Linggang Melapeh Village Linggang Bigung Subdistrict West Kutai District) - WENI ATPRIANI; SYARIFAH AIDA; NDAN IMANG (Universitas Mulawarman (University of Mulawarman), 2018)
Swidden agriculture is a kind of agricultural attempt to function the dry land, without using too much water. This research attempted to discover the production cost, income, and profit of the unirrigated ricefield and to discover the effect of production cost on profit of unirrigated agricultural ricefields. Sampling method in this research was simple random sampling, the total respondents is 38 farmers who use the method of unirrigated agricultural ricefield. Data that have been taken in this research were primary and secondary data. The results of this research shows the profit of unirrigated ricefield farming was IDR193,788,583.32 cropping season (cs)-1 with the average profit of IDR4,680,321.22 ha-1. The income of farmers was IDR522,047,500.00 cs-1 with the average income of IDR12,621,208.26 ha-1. The production cost was IDR328,273,916.68 cs-1 with average cost of IDR7,941,133.75 ha-1. The conclusion of this research was the production cost influences the profit of unirrigated agricultural ricefield as much as 54.9%, meanwhile 45.1% was influenced by other factors.